A Study of Innovative Features in Scholarly Open Access Journals - Björk, Bo-Christer (JMIR Publications, 2011)
BackgroundThe emergence of the Internet has triggered tremendous changes in the publication of scientific peer-reviewed journals. Today, journals are usually available in parallel electronic versions, but the way the peer-review process works, the look of articles and journals, and the rigid and slow publication schedules have remained largely unchanged, at least for the vast majority of subscription-based journals. Those publishing firms and scholarly publishers who have chosen the more radical option of open access (OA), in which the content of journals is freely accessible to anybody with Internet connectivity, have had a much bigger degree of freedom to experiment with innovations. ObjectiveThe objective was to study how open access journals have experimented with innovations concerning ways of organizing the peer review, the format of journals and articles, new interactive and media formats, and novel publishing revenue models. MethodsThe features of 24 open access journals were studied. The journals were chosen in a nonrandom manner from the approximately 7000 existing OA journals based on available information about interesting journals and include both representative cases and highly innovative outlier cases. ResultsMost early OA journals in the 1990s were founded by individual scholars and used a business model based on voluntary work close in spirit to open-source development of software. In the next wave, many long-established journals, in particular society journals and journals from regions such as Latin America, made their articles OA when they started publishing parallel electronic versions. From about 2002 on, newly founded professional OA publishing firms using article-processing charges to fund their operations have emerged. Over the years, there have been several experiments with new forms of peer review, media enhancements, and the inclusion of structured data sets with articles. In recent years, the growth of OA publishing has also been facilitated by the availability of open-source software for journal publishing. ConclusionsThe case studies illustrate how a new technology and a business model enabled by new technology can be harnessed to find new innovative ways for the organization and content of scholarly publishing. Several recent launches of OA journals by major subscription publishers demonstrate that OA is rapidly gaining acceptance as a sustainable alternative to subscription-based scholarly publishing.